Recovering the origin of the lenticular galaxy NGC3115 using multi-band photometry. Issue Volume 15:Issue S359(2020) (March 2019) - Buzzo, Maria Luísa; Cortesi, Arianna; Werle, Ariel; de Oliveira, Claudia Mendes
Abstract: We perform simultaneous multi-band fitting, using the routine GALFITM, of the galaxy NGC3115, in order to recover the stellar populations of its main components (a bulge, a thin disc and a thick disc). We model 11 bands, from ultraviolet to infrared, in order to take into account the galaxy younger stellar population and the presence of the Active Galactic Nuclei (AGN). We find that the majority of the galaxy baryonic mass belongs to the thick disc, which is also the oldest galaxy component, consistent with results from the literature. Differently from previous works, we find that the bulge has the bluest colour and it is younger than the thick disc, either as a result of recent star formation activity, or AGN feedback, or white dwarf emission in an old stellar population. Finally, we propose that NGC3115 was formed either through a two-phase formation scenario, or via an outside-in quenching of an isolated spiral galaxy, whose thick disc had been heated-up via minor mergers with dwarf satellites.